2014
DOI: 10.1016/j.cej.2014.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced arsenate removal by novel Fe–La composite (hydr)oxides synthesized via coprecipitation

Abstract: h i g h l i g h t sFe-La composite (hydr)oxides were synthesized via coprecipitation method. Fe-La composite (hydr)oxides were effective for arsenate removal from water. As(V) was removed by both precipitation and sorption under acidic condition. As(V) removal was achieved by adsorption under alkaline condition. t r a c tArsenic exists ubiquitously in the environment and has been proved to be of great harm to human health. In this study, a series of Fe-La composite (hydr)oxides were synthesized via a facile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 45 publications
8
33
0
Order By: Relevance
“…Similar observation was also found for Cr(VI) adsorption that removal of Cr(VI) decreased significantly with pH increasing from 9 to 11. Trends of both As(V) and Cr(VI) adsorption on La-modified ceramic granules as a function of pH were consistent with anionic contaminant adsorption on other La-based adsorbents 31,4042 . The dominant As(V) and Cr(VI) species in the solution were all anions under the tested pH range (4–11) 21,22 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar observation was also found for Cr(VI) adsorption that removal of Cr(VI) decreased significantly with pH increasing from 9 to 11. Trends of both As(V) and Cr(VI) adsorption on La-modified ceramic granules as a function of pH were consistent with anionic contaminant adsorption on other La-based adsorbents 31,4042 . The dominant As(V) and Cr(VI) species in the solution were all anions under the tested pH range (4–11) 21,22 .…”
Section: Resultssupporting
confidence: 68%
“…Figure 6 shows the adsorption kinetics of As(V) and Cr(VI) by the La-modified ceramic granules treated at 385 °C. Both kinetics curves exhibited a rapid initial uptake and the adsorption plateaued within ~24 h. The adsorption kinetics of As(V) observed in this research was faster than previously reported results while the adsorption kinetics of Cr(VI) was comparable to Cr(VI) adsorption by other reported La-amended adsorbents 29,31 .
Figure 6Adsorption kinetics for As(V) and Cr(VI) on La-modified granular ceramic materials treated at 385 °C. Solution pH 6.8, As(V) concentration and adsorbent dosage were 20 mg/L and 1.0 g/L, and Cr(VI) concentration and adsorbent dosage were 3 mg/L and 0.5 g/L, respectively.
…”
Section: Resultssupporting
confidence: 57%
“…The point of zero charge (pzc) for Fe-Ag MBON was determined by plotting as final pHinitial pH (pHf-pHi) versus pH, yielded the pzc as the pH where pHf-pHi = 0 according to the method described by Zhang et al [29] 2.4.Batch adsorption experiments Fluoride adsorption experiments by prepared Fe-Ag MBON carried out in batch condition and experimental scale in 100 ml flask while shaking on a shaker-incubator at 180 RPM. Structural analysis of an adsorbent and the information of various functional groups in the adsorbent were conveyed by Fourier transform infrared spectroscopy with spectral grade KBr in an agate mortar (FTIR, FTS-165, BIO-RAD, USA).…”
Section: 3adsorbent Characterizationmentioning
confidence: 99%
“…2. In simpler terms, can be expressed that adsorbents with ball-like nanoparticle has the largest specific surface area compare than nano fragment materials [25]. Fe-Ag with 3:1 molar ratio was micro porous (average pore diameters <2 nm) and other materials with different molar ratio were mesoporous (2nm <average pore diameters> 50 nm) since they showed a hysteresis loop for the desorption isotherm.…”
Section: 2specific Surface Area Of Fe-ag Mbonmentioning
confidence: 99%
See 1 more Smart Citation